2018
DOI: 10.1080/17474124.2018.1503053
|View full text |Cite
|
Sign up to set email alerts
|

Advances in understanding the role of cytokines in inflammatory bowel disease

Abstract: Cytokines represent the key pathophysiologic elements that govern the initiation, progression, and, in some circumstances, the resolution of the inflammation occurring in inflammatory bowel disease (IBD). Areas covered: In this review, we will focus on the main effector and anti-inflammatory cytokines produced in IBD and discuss the results of recent trials in which cytokine-based therapy has been used for treating IBD patients. Expert commentary: The possibility to sample mucosal biopsies from IBD patients an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 102 publications
1
33
0
Order By: Relevance
“…During chronic intestinal inflammation, intestinal epithelial cells (IECs) are exposed to numerous pro-inflammatory and anti-inflammatory cytokines, which are produced by multiple immune and nonimmune cells as well as by IECs themselves. For instance, pro-inflammatory cytokines, such as tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6), alter tight junction activity and contribute to apoptosis of IECs, thus leading to the loss of barrier function [2]. In the early stage of IBD, intestinal barrier is just destroyed, antigens from the intestinal cavity (Mycobacteria, Campylobacter, Helicobacter and Escherichia coli, etc.)…”
mentioning
confidence: 99%
“…During chronic intestinal inflammation, intestinal epithelial cells (IECs) are exposed to numerous pro-inflammatory and anti-inflammatory cytokines, which are produced by multiple immune and nonimmune cells as well as by IECs themselves. For instance, pro-inflammatory cytokines, such as tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6), alter tight junction activity and contribute to apoptosis of IECs, thus leading to the loss of barrier function [2]. In the early stage of IBD, intestinal barrier is just destroyed, antigens from the intestinal cavity (Mycobacteria, Campylobacter, Helicobacter and Escherichia coli, etc.)…”
mentioning
confidence: 99%
“…Multiple immune and inflammatory signaling pathways, including the cytokine-cytokine receptor interaction, TNF signaling pathway, and chemokine signaling pathway, are activated and involved in the process of intestinal inflammation [ 8 , 21 ]. Previous studies have demonstrated that the immune-inflammatory response pathway was closely associated with the pathogenesis of UC [ 22 , 23 ], which is mediated by a complex and dynamic relationship between immune cells and cytokines. For instance, the pathways include cytokine-cytokine receptor interaction, and the TNF signaling pathway was significantly associated with the occurrence and development of UC [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies and patent applications have shown a trend in the search for new drugs that act on specific cytokines that participate in crucial stages in certain diseases or clinical conditions (Jin and Dong, 2013;Ogawa et al, 2014;Oliveira et al, 2017;Bevivino and Monteleone, 2018). Cytokine therapy emerged from the need to enhance immunity for tumors using the lymphocyte activator and proliferative factor, interleukin-2 (IL-2) (Rider et al, 2016).…”
Section: Cytokines As Targets For the Development Of Drugsmentioning
confidence: 99%